Terapi Bermain Plastisin Untuk Meningkatkan Perkembangan Motorik Halus Pada Anak Paud di Kober Thoriqul Jannah - Keysha Nur Shaffa Ap; Rike Rahma Amelia; Dela Yulianti; Ai Nuraliah; Gunawan Angga Saputra; Rian Rahmatulloh; Rifaa Fauzan Rabani; Andan Firmansyah (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Fine motor development in early childhood is a key aspect in the development of sensory skills and motor coordination. Playing with plasticine is considered an activity that has the potential to improve children's fine motor skills. Objective: This study aims to observe the effect of playing with plasticine on fine motor development in pre-school children in Kober Thoriqul Jannah. Method: The research was conducted using observation and documentation methods on 30 children aged 4-6 years who were regularly involved in plasticine playing activities for two months. Observations were carried out before, during and after the plasticine play intervention to observe the development of children's fine motor skills. Result: The results of the study showed a significant increase in children's fine motor development after being involved in plasticine play activities. From observations, we can see an increase in the ability to roll, shape and control plasticine with better precision. Conclusion: Playing with plasticine has a positive influence in improving fine motor development in pre-school children. This activity provides the stimuli needed to improve children's fine motor skills in a fun and creative way. This research confirms the important role of playing with plasticine in the development of fine motor skills in early childhood. The practical implications can be the basis for a more targeted play approach in supporting children's development in pre-school educational institutions.